Wind effect on staggered cylinders of square and rectangular sections with variable longitudinal spacings - Hossain, MKM; Islam, MQ; Mandal, AC; Saha, S (Journal of Mechanical Engineering, 2008)
An experimental investigation of mean pressure distributions on a group of cylinders with square and rectangular cross-sections in a uniform cross flow is presented here. The group consists of one rectangular and two square cylinders of identical dimension. The rectangular cylinder is placed centrally in the upstream side and the other two square cylinders are placed symmetrically in the downstream side with respect to tunnel axis. Surface pressure distributions on the cylinders are measured for various longitudinal spacings of the cylinders. Wind loads are obtained in terms of drag coefficients, lift coefficients and total force coefficients. The drag on an isolated cylinder is higher in general than that on the same cylinder while it becomes part of a group. Keywords: Wind load, staggered cylinders. DOI: 10.3329/jme.v38i0.901 Journal of Mechanical Engineering Vol.38 Dec. 2007 pp.52-57